Life Partner Selection Based on High Criteria from the Perspective of Maqashid Syariah - Arif Husnul Khuluq,; Adi Aprianto,; Musyafi Usman, (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
Many criteria are often used as reasons for choosing a partner. Among them are wealth, lineage, beauty and religion. Some people have the principle of only wanting to marry a partner who has high criteria related to these criteria, so that the effect is to delay marriage or even end up living without a partner. This study aims to analyze this principle by referring to the maqashid sharia perspective. maqashid sharia is a central concept in Islam that highlights the goals or purposes of Islamic law. This research is a qualitative research. The method used in data collection is library research. The results showed that the principle of only wanting to marry a partner who has high criteria can be in harmony with maqashid sharia as long as it is applied realistically and considers sharia principles in decision making when there is a conflict between various maslahat, various mafsadat or between maslahat and mafsadat. And it would be better if it is aimed at achieving His pleasure, even though it is not a necessity. The principle will become inconsistent with maqashid sharia if it is applied without considering these matters.